THE EFFECT OF WORKING CAPITAL FINANCING, MSME INVESTMENT FINANCING AND NON-PERFORMING FINANCING ON BANK PROFIT GROWTH GENERAL SHARIA - Saeful Fachri; Indra Sulistiana; Willy Nurhayadi; Irni Wahyuni (SEAN Institute, 2023)
This research was conducted to determine the variable ratio of MSME Working Capital Financing, MSME Investment Financing, and Non-Performing Financing (NPF) on the Profit Growth of Islamic Commercial Banks in Indonesia for the 2015-2021 period. This type of research is quantitative, the data collection method uses nonparticipant observation with data collection techniques through secondary data. The population is all monthly financial statements of Islamic Commercial Banks in Indonesia obtained from statistical data from the Financial Services Authority (OJK). The samples in this study were taken using the saturated sample method, namely monthly financial reports from January 2015 to December 2021, namely 84 samples. Data analysis technique using multiple linear regression. The results of the statistical analysis show: (1) there is a positive and significant effect of MSME working capital financing on profit growth for Islamic Commercial Banks in Indonesia for the 2015-2021 period, (2) there is a positive and significant influence for MSME investment financing on profit growth for Islamic Commercial Banks in Indonesia for the period 2015-2021, (3) there is no significant effect of non-performing financing on the profit growth of Islamic Commercial Banks in Indonesia for the 2015-2021 period, and (4) there is a positive and significant effect of MSME working capital financing, MSME investment financing and non-performing financing jointly on the profit growth of Islamic Commercial Banks in Indonesia for the 2015-2021 period.